11S Glycinin Up-Regulated NLRP-3-Induced Pyroptosis by Triggering Reactive Oxygen Species in Porcine Intestinal Epithelial Cells - Wang, Lei; Sun, Zhifeng; Xie, Weina; Peng, Chenglu; Ding, Hongyan; Li, Yu; Feng, Shibin; Wang, Xichun; Zhao, Chang; Wu, Jinjie (Frontiers in Veterinary Science, 2022)
11S glycinin is a major soybean antigenic protein, induces human and animal allergies. It has been reported to induce the intestinal porcine epithelial (IPEC-J2) cells apoptosis, but the role of pyroptosis in 11S glycinin allergies remains unknown.In this study, IPEC-J2 cells were used as an in vitro physiological model to explore the mechanism of 11S glycinin-induced pyroptosis. The cells were incubated with 0, 1, 5, and 10 mg·mL−1 11S glycinin for 24 h. Our results revealed that 11S glycinin significantly inhibited cell proliferation, induced DNA damage, generated active oxygen, decreased mitochondrial membrane potential and increased the NOD-like receptor protein 3 (NLRP-3) expression of IPEC-J2 cells in a dose-dependent manner. Then, IPEC-J2 cells were transfected with designed sh-NLRP-3 lentivirus to silence NLRP-3. The results showed that 11S glycinin up-regulated the silenced NLRP-3 gene and increased the expression levels of apoptosis-related spot-like protein (ASC), caspase-1,the cleaved GSDMD (gasdermin D) and interleukin-1β (IL-1β). The IPEC-J2 cells showed pyrolysis morphology. Moreover, we revealed that N-acetyl-L-cysteine (NAC) can significantly inhibit the production of ROS and reduce the expression levels of NLRP-3 and the cleaved GSDMD. Taken together, 11S glycinin up-regulates NLRP-3-induced pyroptosis by triggering reactive oxygen species in IPEC-J2 cells.